HUBUNGAN KECEPATAN LARI 40 YARD DAN DAYA LEDAK OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA PUTERI KELAS VIII SMPN 1 PUJUD KECAMATAN PUJUD - Joko Rianto; Ramadi '; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is the low long jump result squat styles of the female students in SMPN 1 Pujud. Of KKM targeted not all students are able to achieve. This problem can be seen from the observation of researcher during school learning, it is suspected because of the 40 yard speed running and leg muscle explosive power possessed by the students. Therefore, the purpose of this study was to determine whether there is a corelation 40 yard speed running and explosive power leg muscles with the long jump squat style results female student of class VII SMPN 1 Pujud. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As independent variables (X1) is the 40 yard speed running, (X2) of leg muscle explosive power, while the dependent variable (Y) is a long jump squat style. The research data was obtained from the results of the test measurements 40 yard running, standing broad jump test and long jump squat style test. The sample in this study were female students of SMPN 1 Pujud who totaled 15 people (purposive sampling). Based on the research results can be concluded as follows: rx1.y obtained amounted to 0.92 correlation with the 40 yards speed running with long jump results squat style female student of class VIII SMP Negeri 1 Pujud Pujud District, and r x2.y amounted to 0.96 there is a correlation explosive power leg muscles with the ong jump squat style results female students of class VIII SMP Negeri 1 Pujud Pujud District., rx1x2 amounted to 0.98 and 0.97 rx1x2.y correlation 40 yards speed running and explosive power leg muscles with the long jump squat style results female students class VIII SMP Negeri 1 Pujud District of Pujud with rtabel 0.514pada significant level α = 0:05. means rhitung> rtabel,Keywords : Speed Running 40 yards. Explosive Power Leg Muscles, Long Jump, Squat Style